Intelligent Controller for Mitigating Power Quality Issues in Hybrid Fuzzy Based Microgrid Applications - Kumar, Naresh; Siddiqui, Anwar Shahzad; Singh, Rajveer (International Journal of Intelligent Systems and Applications in Engineering, 2023)
An intelligent controller for the enhancement of power quality of a hybrid energy source based microgrid that encompasses Wind-PV-Battery is discussed in this work. Global warming coupled with climate change, is one of the most critical crisis that the world faces today. Transitioning to renewable energy sources for power generation, like solar and wind, minimises carbon emissions and aids in tackling climate change. For ensuring a stable and uninterrupted supply of power, a Battery Energy Storage System (BESS) is added to microgrid in order to overcome the intermittency and instability associated with both Wind Energy Conversion System and PV. The PV output voltage is transformed to anticipated level by employing Interleaved Boost Converter (IBC) with excellent efficiency and voltage gain. Conversion efficiency of PV system is heightened by the application of CFLC based MPPT technique, which facilitates a transference of maximum power grid. The AC output from Doubly Fed Induction Generator (DFIG) built WECS is converted to DC using a PWM rectifier controlled by Proportional Integral (PI) controller. The charging and discharging of the battery are effectively carried out using a Battery converter with bidirectional power flow capability. The control of the Battery converter for managing State of Charge (SOC) of battery is accomplished with an aid of PI controller. Conversion of stable DC to AC voltage is established using Voltage Source Inverter (VSI) and minimization of harmonics is achieved using LC filter. The grid voltage synchronization is also performed successfully utilizing PI controller. The proposed hybrid microgrid is simulated by MATLAB and the effective performance of suggested control approach in maintaining the power quality and stability of the microgrid is verified.